"Here's Where I Belong" Still, play adaptation of 'East of Eden.' - Friedman-Abeles Photos:::Creator::::::::::::
From left: Abra Bacon (Heather MacRae), Aron Trask(Ken Kercheval), Cathy/Kate Ames (Nancy Wickwire), Adam Trask (Paul Rogers), Lee (James Coco), and Cal Trask (Walter McGinn). This play is an adaptation of John Steinbeck's 'East of Eden.' It ran for twenty previews and one night at the Billy Rose Theatre in New York. RESTRICTED USEDigital copy only. No hard copy.